Treatment evaluation of the recirculating water systems in coffee fruits (Coffea arabica L.) processing - Raggi, Luiz Gustavo de Rezende; Matos, Antonio Teixeira de; Luiz, Fátima Aparecida Resende (Coffee Science - ISSN 1984-3909, 1970)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-family:Consolas; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Calibri; mso-bidi-theme-font:minor-latin; mso-fareast-language:EN-US;} .MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->This study was carried out in order to evaluate treatment systems for removal of solids and organic material of the water (ARC) in way to make possible its recirculation in the coffee fruits processing. The recirculation of ARC was operated in four circuits: short circuit, without screen (CC-SP), when the ARC was recirculated without any treatment; short circuit, with screen (CC-CP), when the ARC went by a pressurized mesh screen; long circuit, without screen (CL-SP), when the ARC went by a decantation tank; and long circuit, with screen (CL-CP), when the ARC went by pressurized mesh screen and later for the decantation tank. The screen, included to ARC treatment system, showed low efficiency in removing CE, ST, SS, DBO and DQO, not resulting in significant effects in the quality of the water in recirculation. However, the decantation tank was more efficient in the removal of the analyzed variables. The circuit CL-CP presented small increment in the removal efficiencies, compared to CL-SP, not justifying the inclusion of the screen in the process. Thus the obtained data evidence the application only the decantation tank is sufficient in the ARC treatment for recirculation in the coffee fruits (Coffea arabica L.) processing.